2018
DOI: 10.1111/jam.14023
|View full text |Cite
|
Sign up to set email alerts
|

Statistical enhancement of lipase extracellular production byBacillus stratosphericusPSP8 in a batch submerged fermentation process

Abstract: The RSM-CCF statistical optimization is useful for optimizing a large number of variables and studying their interactive effects on extracellular lipase production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…But it was in contradiction with Kim et al 25 who reported the optimum temperature range of B. glycinifermentans as 15-55˚C. Our results are in contradiction with the studies of Shivaji et al 28 and Ismail et al 29 who reported its optimum growth conditions of lipase producing Bacillus species as 8-37˚C, pH 6-10 and 34.8˚C, and pH 6.98, respectively. B. glycinifermentans-MK840989 cells were induced by olive oil (Figure 2) which agrees with Liaqat et al 19 but contradicts with the findings of Iqbal and Rehman, 9 who observed slow growth of B. subtilis I-4 cells in the presence of olive oil.…”
Section: Lipase Quantification and Selectioncontrasting
confidence: 99%
“…But it was in contradiction with Kim et al 25 who reported the optimum temperature range of B. glycinifermentans as 15-55˚C. Our results are in contradiction with the studies of Shivaji et al 28 and Ismail et al 29 who reported its optimum growth conditions of lipase producing Bacillus species as 8-37˚C, pH 6-10 and 34.8˚C, and pH 6.98, respectively. B. glycinifermentans-MK840989 cells were induced by olive oil (Figure 2) which agrees with Liaqat et al 19 but contradicts with the findings of Iqbal and Rehman, 9 who observed slow growth of B. subtilis I-4 cells in the presence of olive oil.…”
Section: Lipase Quantification and Selectioncontrasting
confidence: 99%
“…Response surface methodology was used to optimize the screened variables and studying their interaction effects for enhanced lipase production by SSF. This method involves performing the statistically designed experiments, estimating the mathematical coefficients, predicting the response and checking the adequacy of the model [26]. Design Expert v9.0.5.1 is used to design the experiments of Central Composite Face-Centered Design.…”
Section: Central Composite Face-centered Designmentioning
confidence: 99%
“…Several bacteria produce lipases that can hydrolyze triglycerides [ 41 ]. Bacteria belonging to various genera are widely reported for the production of lipases [ 42 ]. Among them, the extracellular lipases produced by Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%